Impact of computerized accounting information system on small and medium enterprises In Mogadishu, Somalia: the balance scorecard perspectives - Salad Abdule, Abdisalam; Zainol, Zaini; Ahmad @ Abdul Mutalib, Hawa (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Information, communication and technology (ICT) adoption has increased dramatically over time irrespective of organizations, be public or private, profit or not for profit organizations around the world. No doubt that ICT investment will spur economic growth as studied done by many countries. The African Union Agenda 2063 has acknowledged the importance of digital inclusivity for African countries to be on par with the rest of the world as an information society. African nation and Somalia particularly have still some challenges to deploy ICT on the concern of availability, accessibility and affordability. Nevertheless, in a business environment where businesses compete in the highly fragile market, ICT modernization in all business processes including accounting is a crucial tool for continuous improvement towards competitive services offered to customers. The implementation and adaption computerized accounting systems (CAIS) for any organization such as SMEs will enable the management and owners to improve decision making, internal controls and financial information, as well as enable financial reporting to be designed and processed on a standardized format and timely. It was reported that the use of inefficient information to support financial decision making and poor quality and reliability of financial information were part of the major SMEs challenges. Therefore, this study attempts to understand the usage of CAIS and its impact on the performance of SMEs in Somalia. The survey questionnaire is designed and distributed to selected SMEs in the capital city of Mogadishu, Somalia. The results of CAIS’s impact are discussed from four components of balanced scorecard namely financial, customer, internal processes and learning & growth perspectives. The results of this study may provide knowledge about the impact of usage CAIS for SMEs performance in Somalia